Ceftriaxone 1 g Versus 2 g Daily for the Treatment of Enterobacterales Bacteremia: A Retrospective Cohort Study. (December 2022) - Baalbaki, Nadeem; Blum, Sharon; Akerman, Meredith; Johnson, Diane
Background: Ceftriaxone is a commonly used antibiotic for the treatment of susceptible Enterobacterales infections. There is currently limited clinical data on the optimal dose of ceftriaxone for Enterobacterales bacteremia.Objectives: To evaluate the rate of clinical failure of ceftriaxone 1 g versus 2 g daily in patients with Enterobacterales bacteremia.Methods: This was a retrospective cohort study of patients admitted to any of the 3 New York University Hospitals: Long Island, Tisch, or Brooklyn, with ceftriaxone-susceptible Enterobacterales bacteremia, receiving ceftriaxone 1 or 2 g daily from October 2019 to September 2020. The primary outcome was 90-day rate of clinical failure. Clinical failure was defined as escalation of therapy, relapse of infection, or all-cause mortality.Results: A total of 124 patients, 58% in the 1-g group and 42% in the 2-g group, were included. There was no statistically significant difference found in the primary outcome. The 90-day rate of clinical failure was 16.7% versus 9.6%, P = 0.260. There were no statistically significant secondary outcomes, although infection relapse rates at 90 days were numerically greater in the 1-g group (11.1% vs 1.9%, P = 0.078). Hypoalbuminemia was the only variable associated with an increased risk of clinical failure (odds ratio = 4.03; 95% confidence interval [CI] = 1.12-14.50, P = 0.033).Conclusion: In our exploratory findings, there was no statistically significant difference with the 90-day rate of clinical failure between ceftriaxone 1 g versus 2 g daily, although there was a numeric trend toward an increased rate of infection relapse within the 1-g group. Hypoalbuminemia was associated with an increased risk of clinical failure. Prospective studies are warranted to confirm these findings.